2007
DOI: 10.1038/sj.ki.5002296
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 targeting of NF-κB suppresses high glucose-induced MCP-1 expression in mesangial cells

Abstract: Macrophages accumulate in kidney glomeruli and interstitium of patients with diabetic nephropathy in response to monocyte chemoattractant protein-1 (MCP-1); a chemokine produced by both tubular epithelial and mesangial cells (MCs). Vitamin D and its analogs have been shown to have renoprotective effects; however, there are few studies involving diabetic nephropathy. We explored mechanisms by which 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) can be renoprotective by measuring MCP-1 expression in MCs. Using a lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 44 publications
6
133
1
2
Order By: Relevance
“…Changes in ␣-tropomyosin and in the NF-B pathway, which have been linked with ventricular hypertrophy (31,32), were also positively modified by PC. This is consistent with the finding that 1,25(OH) 2 D 3 significantly blunts the activation of NF-B signaling in vitro (33). Finally, cardiac renin gene expression was attenuated by PC, a finding consistent with Li et al (6,34) (35), and mast cells contain the VDR (36).…”
Section: Discussionsupporting
confidence: 81%
“…Changes in ␣-tropomyosin and in the NF-B pathway, which have been linked with ventricular hypertrophy (31,32), were also positively modified by PC. This is consistent with the finding that 1,25(OH) 2 D 3 significantly blunts the activation of NF-B signaling in vitro (33). Finally, cardiac renin gene expression was attenuated by PC, a finding consistent with Li et al (6,34) (35), and mast cells contain the VDR (36).…”
Section: Discussionsupporting
confidence: 81%
“…Monocyte/macrophage infiltration into the kidney, stimulated by MCP-1 produced from kidney cells in diabetic state, promotes kidney fibrosis and renal injury through secretion of inflammatory cytokines. Although vitamin D alone can directly suppress the high-glucose induction of TGF-␤ and MCP-1 in mesangial cells (50), this study showed that cotreatment with losartan and paricalcitol achieved better inhibition of these cytokines in vivo. Because TGF-␤ and MCP-1 are up-regulated by Ang II, the suppression of these factors by the cotreatment is likely mediated by the blockade of Ang II accumulation (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…High glucose, for instance, stimulates MCP1 gene expression by activating AP1 (5), or protein kinase C (PKC) and NF-kB (6), in peritoneal mesothelial cells. High glucose also increases MCP1 mRNA levels in renal mesangial cells through NF-kB activation (7), which provides insight into understanding the development of diabetic nephropathy. In renal proximal tubular cells, albumin induces MCP1 expression by producing reactive oxygen species and, in turn, activating NF-kB when the cells are treated with an excess of albumin (8).…”
mentioning
confidence: 99%